2023
DOI: 10.1108/md-02-2022-0233
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between characteristics of the source of knowledge and knowledge transfer performance: moderated mediation examination of political skill

Abstract: PurposeThe purpose of this research is to explore how knowledge source and knowledge recipient influence knowledge transfer performance through political skill and partnership quality, and in so doing to make up for the lack of research on the political skills of knowledge sources in the process of knowledge transfer.Design/methodology/approachThis research used paired-sample questionnaires to conduct a survey. One direct supervisor was paired with 1–4 subordinates; 224 other-reported questionnaires were sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This is done by examining the associations between constructs since the test does not depend on the variables' orders (Li et al, 2022). As hypothesised in the initial sections of this study, 7, as an indicator of statistical significance, p<0.05 is a condition associated with a highly significant and meaningful association (Hung and Lee, 2022). The correlation test used to understand the behaviour of each BMC element is Kendall tau-b, which is highly effective in studying the direction and strength of associations (Martins Gnecco et al, 2023).…”
Section: Relationships Between the Bmc Elementsmentioning
confidence: 99%
“…This is done by examining the associations between constructs since the test does not depend on the variables' orders (Li et al, 2022). As hypothesised in the initial sections of this study, 7, as an indicator of statistical significance, p<0.05 is a condition associated with a highly significant and meaningful association (Hung and Lee, 2022). The correlation test used to understand the behaviour of each BMC element is Kendall tau-b, which is highly effective in studying the direction and strength of associations (Martins Gnecco et al, 2023).…”
Section: Relationships Between the Bmc Elementsmentioning
confidence: 99%
“…Political skill is defined as "an interpersonal style construct that combines social astuteness with the ability to relate well and otherwise demonstrate situationally appropriate behavior in a disarmingly charming and engaging manner that inspires confidence, trust, sincerity, and genuineness" (Ferris et al, 2000, p. 30). Political intelligence encompasses having the ability to comprehend individuals in a professional environment (Hung, Tian, & Lee, 2023). It has been observed that individuals having political skills are better at impression management, especially in a new environment, and perform better (Munyon et al, 2021;Summers et al, 2020).…”
Section: Political Skills As Moderatormentioning
confidence: 99%
“…African countries vary greatly in their political systems, social characteristics, and ethnicity. During the evolution of an enterprise, the organization can be viewed as akin to a political milieu (Hung et al ., 2023). This study examines expatriate African employees in the financial sector, specifically in the banking industry.…”
Section: Introductionmentioning
confidence: 99%